Non-viral generation of transgenic non-human primates via the piggyBac transposon system - Masataka Nakaya; Chizuru Iwatani; Setsuko Tsukiyama-Fujii; Ai Mieda; Shoko Tarumoto; Taro Tsujimura; Takuya Yamamoto; Takafumi Ichikawa; Tomonori Nakamura; Ichiro Terakado; Ikuo Kawamoto; Takahiro Nakagawa; et al. (Nature Communications)
Abstract Non-human primates, such as cynomolgus monkeys, are invaluable experimental models for understanding human biology and disease. Their close genetic relationship to humans makes them essential for studying fundamental human developmental processes and disease progression. Although lentiviral methods for generating transgenic monkeys exist, several inherent technical difficulties limit their utility. To solve this problem, here we establish a non-viral method for generating transgenic cynomolgus monkeys using the piggyBac transposon system. After optimizing our protocol in mice, we show that the co-injection of piggyBac components with sperm into metaphase II-stage oocytes successfully generates transgenic monkeys expressing transgenes throughout their whole bodies. Transgene expression is observed in all examined tissue types, including germ cells, although the levels of expression vary. Insertion analysis further confirms the successful integration of the transgene. We propose that our method will be a practical non-viral protocol for generating transgenic non-human primates.